(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
This article delves into the multifaceted role of proverbs in communication, analyzing their cognitive and cultural significance within both oral and written discourse. We explore how proverbs function as potent tools for conveying complex ideas, fostering shared understanding, enhancing persuasion, and enriching the overall impact of language. The article examines the unique advantages of proverbs in both spoken and written contexts, highlighting their contributions to clarity, engagement, and cultural connection.